An erosion-resistant magnetic product coating and method of making the same
Patent Information
- Application Number
- CN202310050394.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-01
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-02-01
AI Technical Summary
而现有技术中的涂料在高温环境中不稳定,阻燃性能差,不能起到阻燃的作用
[0023]The anti-erosion magnetic product coating of the present invention comprises component A, which is composed of flame retardant and magnetic powder, and component B, which is composed of fluororesin, modified polytetrafluoroethylene micro powder, and other additives. Components A and B are mixed and used to achieve anti-erosion and flame retardant effects.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating technology, specifically to an anti-erosion magnetic product coating and its preparation method. Background Technology
[0002] Paint is a material that can be applied to the surface of an object using different construction techniques to form a firmly adhered, continuous solid film with a certain strength, which serves as a protective, decorative, or other special function (such as erosion resistance or flame retardancy).
[0003] Erosion resistance refers to the ability of a coating to resist erosion and wear. Erosion damage refers to a type of wear phenomenon in which the surface of a material is damaged due to the impact of flowing particles. Erosion wear can lead to material damage or even scrap, and improving the erosion resistance of coatings is becoming a key research challenge for the future.
[0004] Flame retardancy works by absorbing heat, covering the flame, inhibiting chain reactions, and using non-combustible gases to suffocate the fire, thus preventing or delaying its spread. However, existing coatings are unstable in high-temperature environments, have poor flame retardant properties, and cannot effectively retard the fire. Summary of the Invention
[0005] The purpose of this invention is to provide an anti-erosion magnetic product coating and its preparation method, so as to solve the problems existing in the prior art.
[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution:
[0007] An anti-erosion magnetic product coating, comprising component A and component B; component A comprises a flame retardant and magnetic powder; component B comprises active micro powder, fluororesin, diluent, pigment, dispersant, and defoamer.
[0008] Furthermore, the flame retardant is prepared by reacting 4-bromophenylphenol, phosphorus trichloride, aminomethyltriethoxysilane, and 3-aminomethyltriethoxysilane.
[0009] Furthermore, the fluororesin is prepared from perfluoro(4-methyl-2-pentanoic acid), diethylenetriamine, and glycidyl methacrylate; the active micro powder is prepared by reacting modified polytetrafluoroethylene micro powder.
[0010] Furthermore, the modified polytetrafluoroethylene micro powder is prepared by reacting polytetrafluoroethylene micro powder with octenedioic acid; the particle size of the polytetrafluoroethylene micro powder is 5-20 μm.
[0011] Furthermore, the magnetic powder is nano-iron oxide; the diluent is butyl acetate; the pigment is titanium dioxide, iron yellow, phthalocyanine blue, phthalocyanine green, iron red, or carbon black; the dispersant is isopropyl tris(dioctyl pyrophosphate) titanate; and the defoamer is organosilicon defoamer BYK-066N.
[0012] Furthermore, a method for preparing an erosion-resistant magnetic product coating includes the following preparation steps:
[0013] (1) Mix 4-bromophenylphenol and phosphorus trichloride in a mass ratio of 1:1 to 1:2, reflux at 100 to 200 rpm and 110 to 130 °C for 1 to 3 h, then heat to 150 to 170 °C, add zinc chloride at 0.01 to 0.03 times the mass of 4-bromophenylphenol, continue the reaction for 1 to 3 h, then heat to 200 to 220 °C, continue the reaction for 1 to 3 h, then add deionized water at 0.4 to 0.6 times the mass of 4-bromophenylphenol and anhydrous ethanol at 0.7 to 0.9 times the mass of 4-bromophenylphenol, react at 100 to 200 rpm and 40 to 50 °C for 30 to 60 min, cool to room temperature, filter, wash 3 to 5 times with deionized water, vacuum dry at 10 to 20 Pa and 50 to 70 °C for 7 to 9 h, and recrystallize with tetrahydrofuran to obtain phosphorus oxide cyclide;
[0014] (2) Mix phosphorus oxide cyclase and aminomethyltriethoxysilane at a mass ratio of 1:1.1 to 1:1.5, react at 100 to 120°C for 2 to 4 hours, cool to room temperature, filter, and wash with deionized water 3 to 5 times to obtain intermediate product 1; mix intermediate product 1, 3-aminomethyltriethoxysilane, and tetramethylammonium hydroxide solution at a mass ratio of 1:1:80 to 1:2:100, wherein the mass ratio of tetramethylammonium hydroxide to deionized water in the tetramethylammonium hydroxide solution is 1:20, react at 75 to 95°C under a nitrogen atmosphere for 8 to 14 hours, reduce the pressure to 10 to 20 Pa, continue the reaction for 5 to 7 hours, raise the temperature to 200°C, react for 1 to 2 hours, and cool to room temperature to obtain flame retardant;
[0015] (3) Mix the nitrogen heterocyclic compound, glycidyl methacrylate, diethylene glycol dimethyl ether, and benzoyl peroxide in a mass ratio of 3:1:6:0.05 to 9:7:6:0.05. Stir at 100 to 200 rpm for 10 to 20 min, react at 80 to 100 °C for 7 to 9 h under a nitrogen atmosphere, cool to 60 °C, add trichlorotrifluoroethane (twice the mass of the nitrogen heterocyclic compound) and deionized water (twice the mass of the nitrogen heterocyclic compound), let stand for 2 h, take the lower layer solution, and vacuum dry at 10 to 20 Pa and 50 to 60 °C for 7 to 9 h to obtain fluororesin;
[0016] (4) Mix the pretreated micro powder and acetone glycerol at a mass ratio of 1:10 to 2:10, stir at 100 to 200 rpm for 10 to 20 min, and then add an octenedia acid mixture with a mass ratio of 1:0.0001:0.5 to 3:0.0010:0.5. React under a nitrogen atmosphere at 100 to 200 rpm and 60 to 80 °C for 4 to 6 h, then extract with acetone for 48 h and dry at 60 °C for 6 h to obtain modified polytetrafluoroethylene micro powder;
[0017] (5) Nano-iron oxide and flame retardant are mixed at a mass ratio of 0.5:1 to 1.5:1 to obtain component A; active micro powder, fluororesin, butyl acetate, pigment, titanate solution, and organosilicon defoamer BYK-066N are mixed at a mass ratio of 4:50:3:1:1:1 to 9:80:5:1:5:5, and the mass ratio of isopropyltris(dioctylpyrophosphoryloxy)titanate and anhydrous ethanol in the titanate solution is 1:100 to 4:100. Stir at 600 to 800 rpm for 1 to 2 hours to obtain component B; component A and component B are encapsulated separately to obtain an erosion-resistant magnetic product coating.
[0018] Further, the method for preparing the nitrogen heterocyclic compound in step (3) is as follows: perfluorinated (4-methyl-2-pentanoic acid) and diethylenetriamine are mixed at a mass ratio of 1:1.0 to 1:1.5, reacted at 8 kPa and 150 to 170 °C for 3 to 5 h, then heated to 190 to 210 °C and reacted at 5 kPa under a nitrogen atmosphere for 3 to 5 h, and then cooled to room temperature to prepare the nitrogen heterocyclic compound.
[0019] Furthermore, the pretreatment method for preparing the micro powder in step (4) is as follows: polytetrafluoroethylene micro powder is subjected to an air atmosphere... 60 After irradiation with Co source gamma rays for 0.5–1.5 min, pretreated micro powder is obtained.
[0020] Further, the method for preparing the active micro powder in step (5) is as follows: the modified polytetrafluoroethylene micro powder and sulfoxide are mixed at a mass ratio of 0.05:1 to 0.25:1, heated to 75 to 95°C, reacted for 1 to 2 hours, washed 2 to 4 times with deionized water, and dried at 60°C for 2 to 4 hours to obtain the active micro powder.
[0021] Furthermore, the coating prepared by the method of preparing the anti-erosion magnetic product coating is used by mixing component A and component B at a mass ratio of 1:0.1 to 1:0.3, stirring at 200 to 300 rpm for 15 minutes, and letting it stand for 10 minutes before use.
[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0023] The anti-erosion magnetic product coating of the present invention comprises component A, which is composed of flame retardant and magnetic powder, and component B, which is composed of fluororesin, modified polytetrafluoroethylene micro powder, and other additives. Components A and B are mixed and used to achieve anti-erosion and flame retardant effects.
[0024] First, the flame retardant is prepared by reacting 4-bromophenylphenol, phosphorus trichloride, aminomethyltriethoxysilane, and 3-aminomethyltriethoxysilane. After the hydroxyl group in 4-bromophenylphenol reacts with the chlorine group in phosphorus trichloride, esterification is performed to obtain a phosphorus oxide cyclic compound. The phosphorus oxide cyclic compound decomposes into phosphorooxyic acid upon heating, promoting resin dehydration and carbonization to form a graphite-like coke layer. This layer blocks oxygen and heat sources, slowing down the thermal decomposition of the substrate and giving the coating a flame-retardant effect. The bromine group in 4-bromophenylphenol reacts with the aminomethyltriethoxysilane... After the amino group in ethoxysilane reacts to form an amino group, it polymerizes with 3-aminomethyltriethoxysilane through siloxy groups to form a network of polysiloxane chains. Under high temperature, the amino group decomposes endothermically, releasing non-flammable gases such as nitrogen and ammonia, which causes the coke layer to expand, weakening the heat conduction between the substrate and the heat source and enhancing the flame retardant effect. At the same time, the silicon-oxygen bonds in the siloxane chain carbonize to form silicon-carbon bonds, enhancing the thermal stability of the coke layer and increasing the residual carbon content. This synergistic effect with the coke layer enhances the flame retardant effect.
[0025] Secondly, fluoropolymers are prepared by reacting perfluoro(4-methyl-2-pentanoic acid), diethylenetriamine, and glycidyl methacrylate; modified polytetrafluoroethylene (PTFE) micropowder is prepared by reacting PTFE micropowder and octenedic acid; perfluoro(4-methyl-2-pentanoic acid) and diethylenetriamine are synthesized into nitrogen heterocyclic compounds through amidation and cyclization reactions. The adsorption force of the nitrogen heterocycles improves the adhesion between the coating and the substrate, while the perfluoro segments extend outward to reduce the coefficient of friction of the coating and enhance the erosion resistance; fluoropolymers are prepared by double bond polymerization of nitrogen heterocyclic compounds and glycidyl methacrylate, which can... An anti-erosion coating is formed on the substrate surface. The ester groups can improve the adhesion of the coating to the substrate. At the same time, the epoxy groups in glycidyl methacrylate can crosslink with the amine groups of the flame retardant to form a network structure, which increases the crosslinking density of the coating, enhances the coating strength, and improves the anti-erosion performance of the coating. After being irradiated with gamma rays, polytetrafluoroethylene (PTFE) micropowder reacts with the double bonds in octenedioic acid to obtain modified PTFE micropowder. The modified PTFE micropowder can further improve the crosslinking density of the coating through the reaction of carboxyl groups with amino groups in fluororesin. This, combined with the wear resistance of PTFE micropowder, improves the anti-erosion effect. Detailed Implementation
[0026] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0027] To more clearly illustrate the method provided by the present invention, the following embodiments are provided in detail. The test methods for various indicators of the anti-erosion magnetic product coating prepared in the following embodiments are as follows:
[0028] In the examples and comparative examples, components A and B of the anti-erosion magnetic product coatings were mixed at a mass ratio of 1:0.2, stirred at 250 rpm for 15 min, and allowed to stand for 10 min. The mixture was then applied to the surface of a substrate of the same size with a coating thickness of 300 micrometers. After standing for 1 day, the substrate treated with the anti-erosion magnetic product coating was obtained.
[0029] Flame retardant effect: The limiting oxygen index of the coating was tested on the substrate treated with the anti-erosion magnetic product coating according to ASTM D2863.
[0030] Anti-erosion effect: Under an erosion speed of 10 m / s, an erosion distance of 100 mm, and an erosion angle of 90 degrees, the substrate treated with the anti-erosion magnetic product coating was rinsed with deionized water for 5 min. The mass of the samples before and after the test was measured. Both samples were ultrasonically cleaned in anhydrous ethanol for 5 min before and after the test, with an ultrasonic power of 20 kHz. The wear rate was calculated according to the following formula:
[0031] Wear rate (%) = (weight before test - weight after test) / weight before test.
[0032] Example 1
[0033] (1) 4-Bromophenylphenol and phosphorus trichloride were mixed at a mass ratio of 1:1 and refluxed at 100 rpm and 110 °C for 1 h. The temperature was then raised to 150 °C, and zinc chloride with a mass of 0.01 times that of 4-bromophenylphenol was added. The reaction was continued for 1 h, and the temperature was raised to 200 °C. The reaction was continued for 1 h, and deionized water with a mass of 0.4 times that of 4-bromophenylphenol and anhydrous ethanol with a mass of 0.7 times that of 4-bromophenylphenol were added. The reaction was carried out at 100 rpm and 40 °C for 30 min. The mixture was then cooled to room temperature, filtered, washed three times with deionized water, and dried under vacuum at 10 Pa and 50 °C for 7 h. The mixture was then recrystallized from tetrahydrofuran to obtain the phosphorus oxide cyclide.
[0034] (2) Phosphorus oxide cyclizer and aminomethyltriethoxysilane were mixed at a mass ratio of 1:1.1, reacted at 100°C for 2 hours, cooled to room temperature, filtered, and washed three times with deionized water to obtain intermediate product 1; intermediate product 1, 3-aminomethyltriethoxysilane and tetramethylammonium hydroxide solution were mixed at a mass ratio of 1:1:80, the mass ratio of tetramethylammonium hydroxide to deionized water in the tetramethylammonium hydroxide solution was 1:20, reacted at 75°C under a nitrogen atmosphere for 8 hours, then the pressure was reduced to 10 Pa, and the reaction continued for 5 hours. Then the temperature was raised to 200°C, and the reaction was carried out for 1 hour. After cooling to room temperature, the flame retardant was obtained.
[0035] (3) Perfluorinated (4-methyl-2-pentanoic acid) and diethylenetriamine were mixed at a mass ratio of 1:1.0 and reacted at 8 kPa and 150 °C for 3 h. The temperature was then raised to 190 °C and reacted at 5 kPa and nitrogen atmosphere for 3 h. The mixture was then cooled to room temperature to prepare a nitrogen heterocyclic compound.
[0036] (4) Mix the nitrogen heterocyclic compound, glycidyl methacrylate, diethylene glycol dimethyl ether, and benzoyl peroxide in a mass ratio of 3:1:6:0.05. Stir at 100 rpm for 10 min, react at 80 °C under a nitrogen atmosphere for 7 h, cool to 60 °C, add trichlorotrifluoroethane (twice the mass of the nitrogen heterocyclic compound) and deionized water (twice the mass of the nitrogen heterocyclic compound), let stand for 2 h, take the lower layer solution, and vacuum dry at 10 Pa and 50 °C for 7 h to obtain fluororesin;
[0037] (5) The polytetrafluoroethylene micropowder with a particle size of 5 μm was subjected to an air atmosphere, 60 After irradiating with Co source gamma rays for 0.5 min, pretreated micro powder was obtained. The pretreated micro powder and acetone glycerol were mixed at a mass ratio of 1:10 and stirred at 100 rpm for 10 min. Then, an octenedia acid mixture with a mass ratio of 1:0.0001:0.5 of the pretreated micro powder was added. The mixture was reacted at 100 rpm and 60 °C for 4 h under a nitrogen atmosphere. After extraction with acetone for 48 h, the mixture was dried at 60 °C for 6 h to obtain modified polytetrafluoroethylene micro powder.
[0038] (6) Nano-iron oxide and flame retardant are mixed at a mass ratio of 0.5:1 to obtain component A; modified polytetrafluoroethylene micro powder and sulfoxide are mixed at a mass ratio of 0.05:1, heated to 75℃, reacted for 1 h, washed twice with deionized water, and dried at 60℃ for 2 h to obtain active micro powder; active micro powder, fluororesin, butyl acetate, titanium dioxide, titanate solution, and organosilicon defoamer BYK-066N are mixed at a mass ratio of 4:50:3:1:1:1, and the mass ratio of isopropyltris(dioctylpyrophosphoryloxy)titanate and anhydrous ethanol in the titanate solution is 1:100, stirred at 600 rpm for 1 h to obtain component B; component A and component B are encapsulated separately to obtain anti-erosion magnetic product coating.
[0039] Example 2
[0040] (1) 4-Bromophenylphenol and phosphorus trichloride were mixed at a mass ratio of 1:1.5 and refluxed at 150 rpm and 120 °C for 2 h. The temperature was then raised to 160 °C, and zinc chloride with a mass of 0.02 times that of 4-bromophenylphenol was added. The reaction was continued for 2 h, and the temperature was raised to 210 °C. The reaction was continued for 2 h, and deionized water with a mass of 0.5 times that of 4-bromophenylphenol and anhydrous ethanol with a mass of 0.8 times that of 4-bromophenylphenol were added. The reaction was carried out at 150 rpm and 45 °C for 45 min. The mixture was then cooled to room temperature, filtered, washed 4 times with deionized water, and dried under vacuum at 15 Pa and 60 °C for 8 h. The mixture was then recrystallized from tetrahydrofuran to obtain the phosphorus oxide cyclide.
[0041] (2) Phosphorus oxide cyclizer and aminomethyltriethoxysilane were mixed at a mass ratio of 1:1.3 and reacted at 110°C for 3 hours. After cooling to room temperature, the mixture was filtered and washed four times with deionized water to obtain intermediate product 1. Intermediate product 1, 3-aminomethyltriethoxysilane and tetramethylammonium hydroxide solution were mixed at a mass ratio of 1:1.5:90. The mass ratio of tetramethylammonium hydroxide to deionized water in the tetramethylammonium hydroxide solution was 1:20. The mixture was reacted at 85°C under a nitrogen atmosphere for 11 hours. After the pressure was reduced to 15 Pa, the reaction was continued for 6 hours. The temperature was then raised to 200°C and reacted for 1.5 hours. After cooling to room temperature, the flame retardant was obtained.
[0042] (3) Perfluorinated (4-methyl-2-pentanoic acid) and diethylenetriamine were mixed at a mass ratio of 1:1.3 and reacted at 8 kPa and 160 °C for 4 h. The temperature was then raised to 200 °C and reacted at 5 kPa and nitrogen atmosphere for 4 h. The mixture was then cooled to room temperature to prepare a nitrogen heterocyclic compound.
[0043] (4) Mix the nitrogen heterocyclic compound, glycidyl methacrylate, diethylene glycol dimethyl ether, and benzoyl peroxide in a mass ratio of 6:4:6:0.05. Stir at 150 rpm for 15 min, react at 90 °C under a nitrogen atmosphere for 8 h, cool to 60 °C, add trichlorotrifluoroethane (twice the mass of the nitrogen heterocyclic compound) and deionized water (twice the mass of the nitrogen heterocyclic compound), let stand for 2 h, take the lower layer solution, and vacuum dry at 15 Pa and 55 °C for 8 h to obtain fluororesin;
[0044] (5) The polytetrafluoroethylene micropowder with a particle size of 13 μm was subjected to an air atmosphere, 60 After irradiating with Co-source gamma rays for 1 min, pretreated micro powder was obtained. The pretreated micro powder and acetone glycerol were mixed at a mass ratio of 1.5:10 and stirred at 150 rpm for 15 min. Then, an octenedia acid mixture with a mass ratio of 1:0.0006:0.5 of the pretreated micro powder was added. The mixture was reacted at 70°C and 150 rpm for 5 h under a nitrogen atmosphere. After extraction with acetone for 48 h, the mixture was dried at 60°C for 6 h to obtain modified polytetrafluoroethylene micro powder.
[0045] (6) Nano-iron oxide and flame retardant are mixed at a mass ratio of 1:1 to obtain component A; modified polytetrafluoroethylene micro powder and sulfoxide are mixed at a mass ratio of 0.15:1, heated to 85℃, reacted for 1.5h, washed 3 times with deionized water, and dried at 60℃ for 3h to obtain active micro powder; active micro powder, fluororesin, butyl acetate, phthalocyanine blue, titanate solution, and organosilicon defoamer BYK-066N are mixed at a mass ratio of 7:65:4:1:3:3, and the mass ratio of isopropyltris(dioctylpyrophosphoryloxy)titanate and anhydrous ethanol in the titanate solution is 2.5:100, stirred at 700rpm for 1.5h to obtain component B; component A and component B are encapsulated separately to obtain anti-erosion magnetic product coating.
[0046] Example 3
[0047] (1) 4-Bromophenylphenol and phosphorus trichloride were mixed at a mass ratio of 1:2 and refluxed at 200 rpm and 130 °C for 3 h. The temperature was then raised to 170 °C, and zinc chloride with a mass of 0.03 times that of 4-bromophenylphenol was added. The reaction was continued for 3 h, and the temperature was raised to 220 °C. The reaction was continued for 3 h, and deionized water with a mass of 0.6 times that of 4-bromophenylphenol and anhydrous ethanol with a mass of 0.9 times that of 4-bromophenylphenol were added. The reaction was carried out at 200 rpm and 50 °C for 60 min. The mixture was then cooled to room temperature, filtered, washed 5 times with deionized water, and dried under vacuum at 20 Pa and 70 °C for 9 h. The mixture was then recrystallized from tetrahydrofuran to obtain a phosphorus oxide cyclide.
[0048] (2) Phosphorus oxide cyclizer and aminomethyltriethoxysilane were mixed at a mass ratio of 1:1.5, reacted at 120°C for 4 hours, cooled to room temperature, filtered, and washed 5 times with deionized water to obtain intermediate product 1; intermediate product 1, 3-aminomethyltriethoxysilane and tetramethylammonium hydroxide solution were mixed at a mass ratio of 1:2:100, the mass ratio of tetramethylammonium hydroxide to deionized water in the tetramethylammonium hydroxide solution was 1:20, reacted at 95°C under a nitrogen atmosphere for 14 hours, then the pressure was reduced to 20 Pa, and the reaction continued for 7 hours. Then the temperature was raised to 200°C, and the reaction continued for 2 hours. After cooling to room temperature, the flame retardant was obtained.
[0049] (3) Perfluorinated (4-methyl-2-pentanoic acid) and diethylenetriamine were mixed at a mass ratio of 1:1.5 and reacted at 8 kPa and 170 °C for 5 h. The temperature was then raised to 210 °C and reacted at 5 kPa and nitrogen atmosphere for 5 h. The mixture was then cooled to room temperature to prepare a nitrogen heterocyclic compound.
[0050] (4) Mix the nitrogen heterocyclic compound, glycidyl methacrylate, diethylene glycol dimethyl ether, and benzoyl peroxide in a mass ratio of 9:7:6:0.05. Stir at 200 rpm for 20 min, react at 100 °C under a nitrogen atmosphere for 9 h, cool to 60 °C, add trichlorotrifluoroethane (twice the mass of the nitrogen heterocyclic compound) and deionized water (twice the mass of the nitrogen heterocyclic compound), let stand for 2 h, take the lower layer solution, and vacuum dry at 20 Pa and 60 °C for 9 h to obtain fluororesin;
[0051] (5) The polytetrafluoroethylene micropowder with a particle size of 20 μm was subjected to an air atmosphere, 60 After irradiating with Co-source gamma rays for 1.5 min, pretreated micro powder was obtained. The pretreated micro powder and acetone glycerol were mixed at a mass ratio of 2:10 and stirred at 200 rpm for 20 min. Then, an octenedia acid mixture with a mass ratio of 1:10 of the pretreated micro powder was added. The mass ratio of octenedia acid, ferrous ammonium sulfate, and concentrated sulfuric acid in the octenedia acid mixture was 3:0.0010:0.5. The mixture was reacted at 80°C and 200 rpm for 6 h under a nitrogen atmosphere. After extraction with acetone for 48 h, the mixture was dried at 60°C for 6 h to obtain modified polytetrafluoroethylene micro powder.
[0052] (6) Nano-iron oxide and flame retardant are mixed at a mass ratio of 1.5:1 to obtain component A; modified polytetrafluoroethylene micro powder and sulfoxide are mixed at a mass ratio of 0.25:1, heated to 95℃, reacted for 2 hours, washed 4 times with deionized water, and dried at 60℃ for 4 hours to obtain active micro powder; active micro powder, fluororesin, butyl acetate, carbon black, titanate solution, and organosilicon defoamer BYK-066N are mixed at a mass ratio of 9:80:5:1:5:5, and the mass ratio of isopropyltris(dioctylpyrophosphoryloxy)titanate and anhydrous ethanol in the titanate solution is 4:100, stirred at 800 rpm for 2 hours to obtain component B; component A and component B are encapsulated separately to obtain anti-erosion magnetic product coating.
[0053] Comparative Example 1
[0054] The difference between Comparative Example 1 and Example 2 is that step (1) is omitted, and step (2) is changed as follows: 4-bromophenylphenol and aminomethyltriethoxysilane are mixed at a mass ratio of 1:1.3, reacted at 110°C for 3 hours, cooled to room temperature, filtered, and washed four times with deionized water to obtain intermediate product 1; intermediate product 1, 3-aminomethyltriethoxysilane, and tetramethylammonium hydroxide solution are mixed at a mass ratio of 1:1.5:90, with the mass ratio of tetramethylammonium hydroxide to deionized water in the tetramethylammonium hydroxide solution being 1:20, reacted at 85°C under a nitrogen atmosphere for 11 hours, then the pressure is reduced to 15 Pa, and the reaction continues for 6 hours. Then the temperature is raised to 200°C, reacted for 1.5 hours, and cooled to room temperature to obtain the flame retardant. The remaining steps are the same as in Example 2.
[0055] Comparative Example 2
[0056] The difference between Comparative Example 2 and Example 2 lies in step (2). Step (2) is changed to: mixing phosphorus oxide cyclase and aminomethyltriethoxysilane at a mass ratio of 1:1.3, reacting at 110°C for 3 hours, cooling to room temperature, filtering, and washing with deionized water 4 times to obtain the flame retardant. The remaining steps are the same as in Example 2.
[0057] Comparative Example 3
[0058] The difference between Comparative Example 3 and Example 2 lies in step (2). Step (2) is changed to: mixing phosphorus oxide cyclide, 3-aminomethyltriethoxysilane, and tetramethylammonium hydroxide solution at a mass ratio of 1:1.5:90, with the mass ratio of tetramethylammonium hydroxide to deionized water in the tetramethylammonium hydroxide solution being 1:20. After reacting for 11 hours under a nitrogen atmosphere at 85°C, the pressure is reduced to 15 Pa, and the reaction continues for 6 hours. Then, the temperature is raised to 200°C, and the reaction continues for 1.5 hours. Finally, the mixture is cooled to room temperature to obtain the flame retardant. The remaining steps are the same as in Example 2.
[0059] Comparative Example 4
[0060] The difference between Comparative Example 4 and Example 2 is that step (3) is omitted, and step (4) is changed to: Perfluoro(4-methyl-2-pentanoic acid), glycidyl methacrylate, diethylene glycol dimethyl ether, and benzoyl peroxide are mixed in a mass ratio of 6:4:6:0.05, stirred at 150 rpm for 15 min, reacted at 90°C under a nitrogen atmosphere for 8 h, cooled to 60°C, and then trichlorotrifluoroethane (twice the mass of perfluoro(4-methyl-2-pentanoic acid)) and deionized water (twice the mass of perfluoro(4-methyl-2-pentanoic acid)) are added. After standing for 2 h, the lower layer solution is taken and vacuum dried at 15 Pa and 55°C for 8 h to obtain fluororesin. The remaining steps are the same as in Example 2.
[0061] Comparative Example 5
[0062] The difference between Comparative Example 5 and Example 2 is that step (5) is omitted, and step (6) is changed to: nano-iron oxide and flame retardant are mixed in a mass ratio of 1:1 to obtain component A; polytetrafluoroethylene micro powder, fluororesin, butyl acetate, phthalocyanine blue, titanate solution, and organosilicon defoamer BYK-066N are mixed in a mass ratio of 7:65:4:1:3:3, and the mass ratio of isopropyltris(dioctylpyrophosphate)titanate and anhydrous ethanol in the titanate solution is 2.5:100. The mixture is stirred at 700 rpm for 1.5 h to obtain component B; components A and B are encapsulated separately to obtain an anti-erosion magnetic product coating. The remaining steps are the same as in Example 2.
[0063] Comparative Example 6
[0064] The difference between Comparative Example 6 and Example 2 is that step (4) is omitted, and step (6) is changed to: nano-iron oxide and flame retardant are mixed at a mass ratio of 1:1 to obtain component A; modified polytetrafluoroethylene micro powder and sulfoxide are mixed at a mass ratio of 0.15:1, heated to 85°C, reacted for 1.5 h, washed three times with deionized water, and dried at 60°C for 3 h to obtain active micro powder; active micro powder, nitrogen heterocyclic compound, butyl acetate, phthalocyanine blue, titanate solution, and organosilicon defoamer BYK-066N are mixed at a mass ratio of 7:65:4:1:3:3, and the mass ratio of isopropyltris(dioctylpyrophosphoryloxy)titanate and anhydrous ethanol in the titanate solution is 2.5:100, stirred at 700 rpm for 1.5 h to obtain component B; component A and component B are encapsulated separately to obtain an erosion-resistant magnetic product coating. The remaining steps are the same as in Example 2.
[0065] Example of effect
[0066] Table 1 below shows the performance analysis results of the anti-erosion magnetic product coatings of Examples 1 to 3 and Comparative Examples 1 to 6 of the present invention.
[0067] Table 1
[0068]
[0069]
[0070] A comparison of the limiting oxygen index data of the examples and comparative examples in Table 1 reveals that the addition of flame retardants significantly improves the flame retardant performance of the coatings. The reaction of 4-bromophenylphenol and phosphorus trichloride to prepare phosphorus oxide cyclides promotes resin dehydration and carbonization, forming a graphite-like coke layer that blocks oxygen and heat sources, slowing down the thermal decomposition of the substrate and thus giving the coating a flame-retardant effect. The addition of aminomethyltriethoxysilane introduces amine groups into the flame retardant; these amine groups undergo endothermic decomposition, releasing non-flammable gases, causing the coke layer to expand and weakening the thermal conductivity between the substrate and the heat source, thereby enhancing the flame-retardant effect. Furthermore, the carbonization of silicon-oxygen bonds in the network siloxane chains to form silicon-carbon bonds enhances the thermal stability of the coke layer and increases the residual carbon content. In synergy with the coke layer, the flame retardant effect is enhanced. A comparison of the abrasion rate data of the examples and comparative examples in Table 1 reveals that the coating exhibits good erosion resistance. The reaction of perfluorinated (4-methyl-2-pentanoic acid) and diethylenetriamine to synthesize nitrogen heterocyclic compounds improves the adhesion between the coating and the substrate. The epoxy groups in glycidyl methacrylate can crosslink with the amine groups of the flame retardant to form a network structure, increasing the crosslinking density of the coating, enhancing its strength, and improving its erosion resistance. Modification of polytetrafluoroethylene (PTFE) micropowder with gamma rays and octenedic acid further increases the crosslinking density of the coating, synergistically enhancing the abrasion resistance of the PTFE micropowder.
[0071] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No markings in the claims should be construed as limiting the scope of the claims.
Claims
1. An anti-erosion magnetic product coating, characterized in that, The anti-erosion magnetic coating comprises component A and component B; component A comprises flame retardant and magnetic powder; component B comprises active micro powder, fluororesin, diluent, pigment, dispersant, and defoamer. The fluororesin is prepared from perfluoro(4-methyl-2-valeric acid), diethylenetriamine, and glycidyl methacrylate; the active micro powder is prepared by reacting modified polytetrafluoroethylene micro powder. The modified polytetrafluoroethylene (PTFE) micro powder is prepared by reacting PTFE micro powder with octenedioic acid; the PTFE micro powder has a particle size of 5–20 μm. The preparation method of the anti-erosion magnetic product coating includes the following preparation steps: (1) Mix 4-bromophenylphenol and phosphorus trichloride at a mass ratio of 1:1 to 1:2, reflux at 100 to 200 rpm and 110 to 130 °C for 1 to 3 hours, then heat to 150 to 170 °C, add zinc chloride at 0.01 to 0.03 times the mass of 4-bromophenylphenol, continue the reaction for 1 to 3 hours, then heat to 200 to 220 °C, continue the reaction for 1 to 3 hours, then add deionized water at 0.4 to 0.6 times the mass of 4-bromophenylphenol and anhydrous ethanol at 0.7 to 0.9 times the mass of 4-bromophenylphenol, react at 100 to 200 rpm and 40 to 50 °C for 30 to 60 minutes, cool to room temperature, filter, wash 3 to 5 times with deionized water, vacuum dry at 10 to 20 Pa and 50 to 70 °C for 7 to 9 hours, and recrystallize with tetrahydrofuran to obtain phosphorus oxide cyclide; (2) Mix phosphorus oxide cyclase and aminomethyltriethoxysilane at a mass ratio of 1:1.1 to 1:1.5, react at 100 to 120°C for 2 to 4 hours, cool to room temperature, filter, and wash with deionized water 3 to 5 times to obtain intermediate product 1; mix intermediate product 1, 3-aminomethyltriethoxysilane, and tetramethylammonium hydroxide solution at a mass ratio of 1:1:80 to 1:2:100, wherein the mass ratio of tetramethylammonium hydroxide to deionized water in the tetramethylammonium hydroxide solution is 1:20, react at 75 to 95°C under a nitrogen atmosphere for 8 to 14 hours, reduce the pressure to 10 to 20 Pa, continue the reaction for 5 to 7 hours, raise the temperature to 200°C, react for 1 to 2 hours, and cool to room temperature to obtain flame retardant; (3) Mix the nitrogen heterocyclic compound, glycidyl methacrylate, diethylene glycol dimethyl ether, and benzoyl peroxide in a mass ratio of 3:1:6:0.05 to 9:7:6:0.
05. Stir at 100 to 200 rpm for 10 to 20 minutes. React at 80 to 100°C for 7 to 9 hours under a nitrogen atmosphere. Cool to 60°C and add trichlorotrifluoroethane (twice the mass of the nitrogen heterocyclic compound) and deionized water (twice the mass of the nitrogen heterocyclic compound). Let stand for 2 hours. Take the lower layer solution and vacuum dry at 10 to 20 Pa and 50 to 60°C for 7 to 9 hours to obtain fluororesin. (4) Mix the pretreated micro powder and acetone glycerol at a mass ratio of 1:10 to 2:10, stir at 100 to 200 rpm for 10 to 20 min, and then add an octenedia acid mixture with a mass ratio of 1:0.0001:0.5 to 3:0.0010:0.
5. React under a nitrogen atmosphere at 100 to 200 rpm and 60 to 80 °C for 4 to 6 h, then extract with acetone for 48 h and dry at 60 °C for 6 h to obtain modified polytetrafluoroethylene micro powder; (5) Nano-iron oxide and flame retardant are mixed at a mass ratio of 0.5:1 to 1.5:1 to obtain component A; active micro powder, fluororesin, butyl acetate, pigment, titanate solution, and organosilicon defoamer BYK-066N are mixed at a mass ratio of 4:50:3:1:1:1 to 9:80:5:1:5:5, and the mass ratio of isopropyltris(dioctylpyrophosphoryloxy)titanate and anhydrous ethanol in the titanate solution is 1:100 to 4:
100. The mixture is stirred at 600 to 800 rpm for 1 to 2 hours to obtain component B; component A and component B are encapsulated separately to obtain an anti-erosion magnetic product coating. The magnetic powder is nano-iron oxide; the diluent is butyl acetate; the pigment is titanium dioxide, iron yellow, phthalocyanine blue, phthalocyanine green, iron red, or carbon black; the dispersant is isopropyl tris(dioctyl pyrophosphate) titanate; and the defoamer is organosilicon defoamer BYK-066N. The method for preparing the nitrogen heterocyclic compound in step (3) is as follows: perfluorinated (4-methyl-2-valeric acid) and diethylenetriamine are mixed at a mass ratio of 1:1.0 to 1:1.5, reacted at 8 kPa and 150-170°C for 3-5 h, then heated to 190-210°C and reacted at 5 kPa under a nitrogen atmosphere for 3-5 h, and then cooled to room temperature to obtain the nitrogen heterocyclic compound; The pretreated micro powder preparation method in step (4) is as follows: after irradiating polytetrafluoroethylene micro powder in an air atmosphere with 60Co source γ-rays for 0.5~1.5 min, pretreated micro powder is obtained.
2. The anti-erosion magnetic product coating according to claim 1, characterized in that, The method for preparing the active micro powder in step (5) is as follows: the modified polytetrafluoroethylene micro powder and sulfoxide are mixed at a mass ratio of 0.05:1 to 0.25:1, heated to 75 to 95°C, reacted for 1 to 2 hours, washed 2 to 4 times with deionized water, and dried at 60°C for 2 to 4 hours to obtain the active micro powder.
3. The anti-erosion magnetic product coating according to claim 1, characterized in that, The coating prepared by the method described above for anti-erosion magnetic product coating is prepared by mixing component A and component B at a mass ratio of 1:0.1 to 1:0.3, stirring at 200 to 300 rpm for 15 minutes, and letting it stand for 10 minutes before use.
Citation Information
Patent Citations
Self-lubricating thread of oil well pipe
CN101644142A
Fluorocarbon paint with high flame resistance and preparation method thereof
CN108976937A